1998
DOI: 10.1046/j.1365-2796.1998.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiocontrast‐induced natriuresis associated with increased urinary urodilatin excretion

Abstract: Abstract. Haller C, Meyer M, Scheele T, Koch A, Forssmann W-G and Kübler W (University of Heidelberg; and Lower Saxony Institute for Peptide Research, Hanover; Germany). Radiocontrastinduced natriuresis associated with increased urinary urodilatin excretion (original article). J Intern Med 1998; 243: 155-62.Objective. Intravascular radiocontrast agents induce a pronounced diuresis. The aim of the present study was to investigate the (patho-)physiological mechanisms of the radiocontrast-induced diuresis. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…The two latter could be explained by osmotic diuresis-induced dilution. Some studies, in agreement with ours, have shown increased UE Na+ 12,31,32 and FE Na+ 32 after ionic and non-ionic radiological contrast, which seems to be independent of contrast osmolality. Increased sodium excretion cannot be explained by sodium content in radiological contrast: diatrizoate has high sodium concentration, while ioxilan, iopamidol, iohexol and other low osmolality contrasts have very low concentrations of this electrolyte.…”
Section: Another Hypothesis To Explain Radiological Contrast Effects supporting
confidence: 91%
“…The two latter could be explained by osmotic diuresis-induced dilution. Some studies, in agreement with ours, have shown increased UE Na+ 12,31,32 and FE Na+ 32 after ionic and non-ionic radiological contrast, which seems to be independent of contrast osmolality. Increased sodium excretion cannot be explained by sodium content in radiological contrast: diatrizoate has high sodium concentration, while ioxilan, iopamidol, iohexol and other low osmolality contrasts have very low concentrations of this electrolyte.…”
Section: Another Hypothesis To Explain Radiological Contrast Effects supporting
confidence: 91%
“…8,9 We are curious whether Iodixnaol has high direct toxicity on kidney tubular cells, thus contributing to CIN. Moreover, the fact that radiocontrast agents could induce pronounced natriuresis 10 indicates that a contrast agent may cause kidney tubule cell permeability change. In the present study, we investigated whether Iodixanol causes a direct toxicity on cultured renal tubular cells or causes kidney tubular cell junction permeability changes.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast agents are almost exclusively removed by glomerular filtration, reaching the renal tubules at greatly increased concentrations. [32] Therefore, it is possible that the changes in L-arginine and choline transport, evidenced at high radiocontrast concentrations, are relevant to what occurs in kidney tubules on clinical exposure.…”
Section: Discussionmentioning
confidence: 99%